THE FORMATION OF A COMMON INTERNATIONAL LEXICAL FUND OF THE RUSSIAN AND UZBEK LANGUAGES - Urinova Shahlo Abdikhalimovna (Zeta Repository, 2023)
The article is devoted to the process of formation of the international lexical fund of the Russian and Uzbek languages, the purpose of which is the rapprochement of nations. In addition, the topic of the origin of international words is touched upon.